Peran Script Writer Dalam Menyampaikan Pesan Moral Melalui Film Sabda Rindu - Nugraha, Panji; Eriend, Dion (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
This final project is prepared based on the author's experience during the production of a movie entitled "Sabda Rindu". During the pre-production and filming process, the author served as a script writer. The main task of a script writer is to write scripts and develop ideas and adapt a story in the form of a narrative with the aim that the message to be conveyed from a film can be conveyed properly through a dialog or scenario. This film production activity aims to improve the author's ability to communicate, add relationships and be able to apply the knowledge learned during college so as to get a picture of the world of work later. While carrying out film production activities, the author has observed and felt for himself how the process of making a script into a film work. Starting from selecting the storyline, writing dialog to auditioning the selection of roles that are deemed suitable to play the film. So that what is visualized by the script writer can be realized properly by the production team. So that in its application, good communication is needed between the script writer and the team in order to establish good cooperation.Interpersonal communication theory is the process of sending and receiving messages with the aim of getting feedback and reactions so that the message to be conveyed can influence behavior between two or more people. Movies are not only entertainment media, but through movies it is hoped that people can also take moral messages from the movie's story in the real world.